Tryptophan Supplementation Enhances Intestinal Health by Improving Gut Barrier Function, Alleviating Inflammation, and Modulating Intestinal Microbiome in Lipopolysaccharide-Challenged Piglets - Liu, Guangmang; Lu, Jiajia; Sun, Weixiao; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Kim, In Ho; Zhang, Ruinan; Wang, Jing (Frontiers in Microbiology, 2022)
Gut microbiota plays an important role in the metabolism and growth of piglets, and tryptophan (Trp) has been used as a diet supplementation in modifying the gut microbiota. However, there is no information about the effect of Trp on intestinal microbiota after lipopolysaccharide (LPS) challenge. This study aimed to investigate the effect of Trp on intestinal barrier function, inflammation, antioxidant status, and microbiota in LPS-challenged piglets. A total of 18 weaned piglets were randomly divided into three groups, namely, (i) non-challenged control (CON); (ii) LPS-challenged control (LPS-CON); and (iii) LPS + 0.2% Trp (LPS-Trp). On the 35th day of this experiment, pigs in the LPS-CON and LPS-Trp groups were intraperitoneally injected with 100 μg/kg of body weight LPS, while the CON group was injected with sterile saline. At 4 h post-challenge, all pigs were sacrificed, and intestinal samples were collected. The results showed that Trp increased the relative abundance of Anaerostipes (P < 0.05) and tended to increase the relative abundance of V9D2013_group (P = 0.09), while the relative abundance of Corynebacterium (P < 0.05) and unclassified_c__Bacteroidia (P < 0.01) in the colonic digesta decreased. In addition, Trp increased the concentrations of acetate, propionate, butyrate, and isovalerate in the colonic digesta (P < 0.05). Moreover, Trp reduced the mRNA level of proinflammatory cytokines (P < 0.01), and increased the mRNA level of aryl hydrocarbon receptor, cytochrome P450 (CYP) 1A1 and CYP1B1 (P < 0.05). Correlation analysis results showed that acetate, propionate, and butyrate concentrations were positively correlated with mRNA level of occludin and CYP1B1(P < 0.05), and were negatively correlated with pro-inflammatory cytokines gene expression (P < 0.05). Isovalerate concentration was positively correlated with catalase activity (P < 0.05), and was negatively correlated with pro-inflammatory cytokines gene expression (P < 0.05). Furthermore, Trp enhanced the antioxidant activities (P < 0.01), and increased the mRNA and protein expressions of claudin-1, occludin and zonula occludens-1 (P < 0.01). These results suggest that Trp enhanced intestinal health by a modulated intestinal microbiota composition, improved the short chain fatty acids synthesis, reduced inflammation, increased antioxidant capacity, and improved intestinal barrier function.